High-throughput sequencing of nodal marginal zone lymphomas identifies recurrent BRAF mutations. Issue 11 (November 2018) - Pillonel, V.; Juskevicius, D.; Ng, C.; Bodmer, A.; Zettl, A.; Jucker, D.; Dirnhofer, S.; Tzankov, A.
Abstract Nodal marginal zone lymphoma (NMZL) is a rare small B-cell lymphoma lacking disease-defining phenotype and precise diagnostic markers. To better understand the mutational landscape of NMZL, particularly in comparison to other nodal small B-cell lymphomas, we performed whole-exome sequencing, targeted high-throughput sequencing, and array-comparative genomic hybridization on a retrospective series. Our study identified for the first time recurrent, diagnostically useful, and potentially therapeutically relevantBRAF mutations in NMZL. Sets of somatic mutations that could help to discriminate NMZL from other closely related small B-cell lymphomas were uncovered and tested on unclassifiable small B-cell lymphoma cases, in which clinical, morphological, and phenotypical features were equivocal. Application of targeted gene panel sequencing gave at many occasions valuable clues for more specific classification.